The Effectiveness of Listen and Draw Game towards Student’s Motivation in Learning Skill - Mariana Sasmita (Journal of Languages and Language Teaching, 2018)
This research is aimed at to finding The Effectiveness of listen and draw Game towards Students’ Motivation in Learning listening at the Second Grade Students of MTs Aunul Ibad NW Beroro in Academic Year 2017/2018. The method of this research was applied is experimental research (quantitative approach). The population of this research was the students of MTs Aunul Ibad NW Beroro in academic year 2017/2018. The sample of the study was 36 students consist of two classes. The sample technique used in this research was cluster random sampling by using lottery. The technique which used to analysis the data was t-test and r-test formula. From the research data found out that the students’ t-test score (3,97) is highest than that the value of t-table (2.028 ). Based on the result of the study, it can be concluded that the use of listen and draw game is effectiveness in learning listening at second grade students of MTs Aunul Ibad NW Beroro and the result correlation between students’ motivation and listening, it shows r-test (0,99) > r-table (0,468). Based on the result of the study, it can be conclude there is correlation between students’ motivation and listening is accepted. In other word, alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected.